Argentina, 1946-83 - Di Tella, Guido. author. aut Link
X, 219 p.
Keywords: Representing the speeches and papers given by ministers or other authorities at the symposium on Argentina's Economic Policy 1946-1983 held in Toledo, Spain, this collection spans both the economic and political dimensions of the development of Argentinian economic policies.